Pemanfaatan Uang Korupsi untuk Kepentingan Umum: Analisis Fiqh - La Jamaa La Jamaa (Al-Mizan, 2015)
Corruption is an act forbidden in Islamic law, because the money of corruption is dirty money. Therefore, there is no zakat from money of corruption, because criminals instead of the original owners the money of corruption. Ideally, money of corrupt should be returned to the state treasury, though with the risk of perpetrators (criminals) sentenced to prison according mistakes. But if the criminals would repent but do not want to jail, then the money of corruption that are within his power to be returned to the path of Allah, which is used for the public interest, both for the construction of mosques, bridges, hospitals, schools and orphanages purposes and other social interests, but the gift is not as alms from criminals, because it also prohibited from engaging in corruption, though the intention of social interest.